Association Mapping for Aluminum Tolerance in a Core Collection of Rice Landraces - Zhang, Peng; Zhong, Kaizhen; Tong, Hanhua; Shahid, Muhammad Qasim; Li, Jinquan (Frontiers in Plant Science, 2016)
Trivalent aluminum (Al3+) has drastic effect on the rice production in acidic soils. Elite genes for aluminum (Al) tolerance might exist in rice landraces. Therefore, the purpose of this research is to mine the elite genes within rice landraces. Association mapping was performed for Al tolerance traits (relative root elongation) using a core collection of 150 accessions of rice landraces (i.e. Ting’s rice core collection). Our results showed that the Ting’s rice core collection possessed a wide-range of phenotypic variation for Al tolerance, and the index of Al tolerance (relative root elongation) was ranged from 0.22 to 0.89. Moreover, the groups with different origin and different compositions of indica and japonica rice showed different degree of Al tolerance. These rice landraces were further screened with 274 SSR markers and association mapping was performed using a mixed linear model (MLM) approach. The mapping results showed that a total of 23 significant (P<0.05) trait-marker associations were detected for Al tolerance, of those, three (13%) were identical to previous reported QTLs, and the other 20 were reported first time in this study. The 23 significant (P<0.05) associations explained averagely 11.65% of the phenotypic variation (R2), among which the marker PSM365, located on chromosome 11, showed the highest R2 (20.03%). Several elite alleles for aluminum tolerance were found on the basis of multiple comparisons of allelic effects, which could be used for developing rice cultivars with Al tolerance through marker-assisted breeding.